Answer:
64
Step-by-step explanation:
Answer:
x=-4
Step-by-step explanation:
−3(7−2x)+3=8x−10
Step 1: Simplify both sides of the equation.
−3(7−2x)+3=8x−10
(−3)(7)+(−3)(−2x)+3=8x+−10(Distribute)
−21+6x+3=8x+−10
(6x)+(−21+3)=8x−10(Combine Like Terms)
6x+−18=8x−10
6x−18=8x−10
Step 2: Subtract 8x from both sides.
6x−18−8x=8x−10−8x
−2x−18=−10
Step 3: Add 18 to both sides.
−2x−18+18=−10+18
−2x=8
Step 4: Divide both sides by -2.
−2x
−2
=
8
−2
x=−4
Answer: picture see the picture
Step-by-step explanation:
Answer:
<em>− 2sin(b) / cos(2b)</em>
Step-by-step explanation:
DIFFERENTIATE W.R.T. B is a different method entirely
We simply add together the numerators and set with 2cos
then keep this number and add to sinb and square it.
then repeat initial 2 + cosb ^2 but instead of multiplying its add.
Then set the whole division to -sin (2b) squared then +1
<em> − 2cos(b)(3(sin(b))^2+(cos(b))^2) / −(sin(2b)) ^2 +1 </em>